Industrial training report: Orangebeam Construction / Nursyakila Kamal - Kamal, Nursyakila (Universiti Teknologi MARA, Perlis, 2024)
This industrial training report provides an in-depth overview of my six-month internship with Orangebeam Construction, which is situated in Ara Damansara. The purpose of this report is to showcase my industrial training .Together with my biography and the company's profile, this report will also include a training reflection that outlines my duties and responsibilities and roles within the organization. I've included a number of experiences and reflections in my report, which are visible in the section on training reflections. The SWOT Analysis provides an overview of this organization. Regardless of the industry, SWOT analysis is a highly useful study for us to do on an organization. Additionally, it may be analyzed to create methods that will work in the future. In addition to helping us recognize the company's challenges, SWOT analysis may help protect the business from being taken advantage of.